Cervical giant Nabothian cysts in a woman with primary infertility: a case report - Sedigheh Hosseini; Parisa Taherzadeh Boroujeni; Nazanin Hajizadeh; Mahsa Kazemi; Leila Majdi; Hamidreza Mosleh (Journal of Medical Case Reports)
Abstract Background Nabothian cysts are benign cervical lesions commonly observed in women of reproductive age, typically ranging from 2 to 10 mm in diameter and often asymptomatic. These cysts arise from the obstruction of cervical mucous glands, a phenomenon frequently linked to childbirth, minor trauma, or chronic cervicitis. While small Nabothian cysts are usually incidental findings, giant Nabothian cysts—those exceeding 4 cm—are rare and can present diagnostic and therapeutic challenges. Their size and appearance may mimic malignant entities such as adenoma malignum, necessitating advanced imaging and histopathological evaluation. Although their association with infertility remains controversial, some evidence suggests that large cysts might interfere with fertility by obstructing the cervical canal or altering mucus production, which is critical for sperm transport. This report examines a rare case of giant Nabothian cysts in the context of assisted reproductive technology, highlighting their management and potential implications for infertility treatment. Case presentation A 41-year-old Iranian woman with a 2-year history of primary infertility presented to our clinic. She reported regular menstrual cycles and no symptoms such as pelvic pain or abnormal discharge. During her infertility evaluation, transvaginal ultrasonography identified multiple large cervical cysts (20–45 mm) obstructing the cervical os. Subsequent magnetic resonance imaging and biopsy confirmed these as benign Nabothian cysts. Her partner’s semen analysis revealed severe teratozoospermia, prompting the use of intracytoplasmic sperm injection. During oocyte retrieval, the cysts were aspirated to prevent potential complications during embryo transfer. Two high-quality embryos were transferred, but the cycle did not result in pregnancy. Cytological analysis of the aspirated fluid reaffirmed the benign nature of the cysts. Conclusion This case demonstrates that giant Nabothian cysts can be safely aspirated during an assisted reproductive technology cycle, potentially improving procedural outcomes. However, the lack of pregnancy suggests that, while cyst management may address mechanical barriers, it does not guarantee success in multifactorial infertility cases. Further studies are needed to elucidate the role of Nabothian cysts in infertility and refine their management in assisted reproductive technology settings.